New Thermoelectric Sensor Adapted to Realize an Infrared Radiations Detector - Mohammed Rahmoun; Khalid Hachami; Abdelwahad Touil; Benaissa Bellach; Mohammed Bailich; Ammar Merdani (Active and Passive Electronic Components)
The present paper deals with the design and the realization of a new thermoelectric sensor (Seebeck), sensitive to the infrared radiations emitted by different sources. The function mechanism utilizes radiative absorption phenomena, heat transfer, and thermoelectric effects. The sensor includes two printed circuits, the first is a planar thermoelectric circuit constituted of many plated differential thermocouples, and the second is constituted of a resistive constantan track and placed at the top of the first circuit so that the constantan track is placed on the top of the even thermocouple junctions. The constantan track, covered with a resin of great absorptivity, collects the infra-red radiations and generates temperature gradients between the junction points of the first circuit. Then the resulting temperature differences between the junction points are directly converted into a proportional Seebeck voltage. As an application, the sensor is adapted in order to realize a device for detecting infrared radiations, and the results are very encouraging.